FARMING INCOME OF AGRIBUSINESS PALM OIL IN TULANG BAWANG DISTRICT - Yuni Elmita Sari (Jurnal Peternakan (Jurnal of Animal Science), 2020)
The research aims to determine :1 management of palm oil plantation,2) income earned by  oil palm farmers. The research was conduced on august to September 2017 on Tulang Bawang distric. The research was conduced on august to September 2017 on Tulang Bawang distric.. The samples are taken from one hundred fiftytwo farmers who take seventysix self- help palm oil farmers and seventysix plasma oil palm farmers with proportional random sampling.  Analyzing the management of oil palm was used descriptive analysis.  Supply  chain analysis used quantitative descriptive analysis. The results of the research indicate  that: plasma farmer's income is greater than self-help farmers because the smallholders of  the plantation management business are managed by the company well with the payment system of cooperation that has been set so plasma farmers have a certainty in obtaining the results of the agreement with the company